The elderly perception of their life habits and self-care behavior in their youth and the influence of these in health and aging - Ribeiro, Mariana dos Santos (2015)
This study aims to understand life habits that elders had in their youth and the influence of these in health and aging, through qualitative research, Oral History Method. It was observed that get to elders age in good health conditions may be achieved by those who prepared themselves when young to this stage of life, have self-care behavior and take responsibility for their own health.